Elizabeth Jennings : 'the inward war' - Greene, Dana (Oxford University Press, 2018)
Elizabeth Jennings was one of the most popular, prolific, and widely anthologized lyric poets in the second half of the twentieth century. This biography, based on extensive archival research and interviews with Jennings's contemporaries, integrates her life and work and explores the 'inward war' the poet experienced as a result of her gender, religion, and mental fragility. Originally associated with the Movement, Jennings was sui generis, believing poetry was 'communication' and 'communion.' She wrote of nature, friendship, childhood, religion, love, and art, endearing her to a wide audience. Yet lifelong depression, unbearable loneliness, unrelenting fears, poverty, and physical illness plagued her. These were exacerbated by her gender in a male-dominated literary world and an inherited Catholic worldview which initially inculcated guilt and shame. However, a tenacious drive to be a poet made her, 'the most unconditionally loved writer of her generation.' Her life is tracked in her voluminous published and unpublished poetry and prose. The themes of mental illness, the importance of place, the problems associated with being an unmarried woman artist, her relationship with literary mentors and younger poets, her non-feminist feminism, and her marginality and sympathy for the outcast are all explored.